ANALYZING THE IMPACT OF GOODS AND SERVICES TAX ON THE SERVICE SECTOR: A CASE STUDY OF HAVERI DISTRICT, KARNATAKA STATE - Barki, Gururaj S; Ajaraddi, Ramesh B (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Goods and Service Tax (GST) has simplified taxation for service providers, making it easier to comply with regulations. However, small businesses have struggled to adapt, reducing their earnings. GST reduces tax cascading in the service sector, allowing service providers to pass savings on to customers. Despite this, service providers use tax software, hired tax advisors, and enrolled in government training courses to better understand the new tax structure. The streamlined tax structure promotes economic efficiency and transparency, benefiting both consumers and businesses. Service sectors in Haveri District are adjusting to GST by implementing price adjustments, educating consumers, and offering discounts and promotions. This transition has made service sectors more strategic and innovative, making the business climate more competitive and long-lasting. Hence, the present paper analyzes the impact of GST on the service industry in Haveri District.